PLANT MATERIALS TRANSFERRED MANAGEMENT: A PART OF EX-SITU CONSERVATION BUSINESS PROCESS OF CIBODAS BOTANIC GARDENS - Imawan Wahyu Hidayat; Yudi Suhendri (Universitas Mataram, 2020)
Abstract: One of the botanic gardens businesses is socializing cultivated plants from the garden to be further utilized, especially for reforestation (and other conservation purposes), research and educational purposes. This socialization can be conducted through seeds exchange and plant (and parts) that transferred for various users. Cibodas Botanic Gardens (CBG), as one of the Indonesian botanic gardens, is also conducted this activity. Plant materials and so the data needed for these purposes are recorded in the material(s) transfer agreement (MTA). The study aimed to analyze the number, type, and species of transferred plant materials and the data, the background of the applicants and for what purpose of the materials is needed based on MTAÃ¢â¬â¢s documents. This study conducted through a quantitative descriptive method based on the materials transferred from 2013 to 2018. The results described that, for six years, the number of MTA was 86 documents, with 81 applicants. The applicants from local were 92.6% and foreign such as from China, Netherlands and Japan were 7.4%. For six last years, the transferred materials included 1,205 in the form of living plants, 201 specimens in form of herbarium, 8,605 specimens in the form of seeds, many thousands various unit of part of plant, plant propagation unit and other plant materials (i.e. mycorrhiza, fungi/ lichen/ moss, rhizoid and thallus, and ascoma), and 63 unit in the form of data and other information. The results expected to be able to describe the contribution range of CBG, especially in ex-situ plant conservation and the data, both on the local and international scale.Keywords: plant materials; material(s) transfer agreement (MTA); ex-situ plant conservation; Cibodas Botanic Gardens (CBG)